Clinical and Radiological Findings in Patients with Newly Diagnosed Graves' Ophthalmopathy. (3rd May 2021) - Cevik, Yakup; Taylan Sekeroglu, Hande; Ozgen, Burce; Erkan Turan, Kadriye; Sanac, Ali Sefik
Abstract : Background . Graves' ophthalmopathy is the most common extrathyroidal manifestation of Graves' disease. The objective of this study was to investigate the clinical ophthalmological and MRI findings in newly diagnosed Graves' ophthalmopathy. Methods . This study included 36 newly diagnosed Graves' disease patients and 23 control participants. Patients and control participants underwent detailed ophthalmologic examination. In addition, all subjects underwent orbital MRI examination; and sizes, cross-sectional areas, and signal intensities of extraocular muscles were also measured. Results . Based on MRI measurements, the mean exophthalmos in the left eye was significantly higher in the patient group when compared to those of controls (2.04 ± 0.29 vs. 1.85 ± 0.15 cm, p  = 0.003). The mean long diameter of inferior oblique muscle in both the right and left eyes were significantly shorter in patients when compared to those of controls (p  = 0.001, p  = 0.002, resp.); however, the mean long diameter of superior oblique in the left eye was longer in patients than those of controls (p  = 0.001). Patients had significantly higher superior oblique muscle signal intensity than those of controls in the right eye (p  = 0.01). There was no significant difference for the other parameters between the patient and control groups. Conclusion . Our findings suggest that there is no obvious change in MRI examination despite clinical ophthalmological findings in patients with newly diagnosed Graves' ophthalmopathy. Unnecessary MRI examination should be avoided in this patient group due to unsatisfactory cost-effectiveness.